Fertility of frozen-thawed dog sperm with the addition of homologous prostatic fluid or protein-free sperm TALP prior to intravaginal insemination of bitches - Nothling, Johan O. (University of Pretoria, 2013)
Dissertation (MMedVet (Gyn))--University of Pretoria, 2002.